Cystic fibrosis across Europe: EuroCareCF analysis of demographic data from 35 countries - Mehta, Gita R.; Macek, Milan St; Mehta, Anil; Yiallouros, Panayiotis K. (My University, 2010)
Background: A 35 country European cystic fibrosis (CF) demographic registry was developed to compare outcomes (EuroCareCF EC-FP6). Methods: We applied methods that had successfully created country-specific registries inviting wide participation to obtain consent and collate demographic and CFTR genotype data. Results: Among 29,095 patients, a widely different country-specific prevalence of childhood CF exists that cannot be explained by differential population frequency of mutant-CFTR or case under-ascertainment with a significant paucity of the homozygous p.Phe508del genotype that presents in childhood in > 90% of cases. Conclusions: Excess premature childhood CF mortality may still occur. The better resourced Western Europe now has a ~. 5% mortality for childhood CF, which is not apparent in many of the European countries reported here. In addition, a female survival disadvantage exists. The reasons require further investigation. We showcase the value of simple data collection in one rare disease, which might interest those managing rare diseases across the globe.
Keywords: Database; Rare disease; Geography; Chronic disease; Genetics; p.Phe508del; CFTR